The relevance of public policies for the sustainability of community media: Lessons from Argentina - Segura, Maria Soledad (2019)
Since 2004 and for the first time in the history of broadcasting in the region, a dozen Latin American countries have acknowledged community radio and television stations as legal providers of audiovisual communication services. In Argentina, a law passed in 2009 not only awarded legal recognition to the sector, it also provided a promotion mechanism for community media. In this respect, it was one of the most ambitious ones in the region. The driving question is: How relevant are public policies for the sustainability of community media in Argentina? The argument is: even though the sector of community media has developed and persisted for decades in illegal conditions imposed by the state, the legalization and promotion policies carried out by the state from the perspective of human rights in a context of extreme media ownership concentration have been critical to the growth and sustainability of non-profit media.